2020
DOI: 10.1007/s10578-020-01013-5
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Sensory Processing Profiles and Their Associations With Motor Problems In Preschoolers With Developmental Coordination Disorder

Abstract: The aims of this study were to identify sensory processing profiles specific to preschoolers with DCD in a community sample and examine the association of sensory processing problems with motor coordination difficulties in these children. Sixty-three 5-year-old children with DCD and without other neurodevelopmental disorders and 106 age-matched typically developing children participated in this study. Sensory processing problems were assessed using the Sensory Profile. Our results demonstrated problems in wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 41 publications
4
21
0
Order By: Relevance
“…Similarly, sensory challenges directly impact the quality of life [ 14 ], and, therefore, appropriate counseling and early initiation of behavioral interventions can strongly impact patient and family experiences. Finally, many neurodevelopmental disorders have similar or overlapping presentations, and subtle clinical differences, such as sensory features, can be helpful in making a diagnosis or guiding genetic testing [ 3 , 4 , 15 ]. Thus, characterizing the sensory profiles for specific disorders is important for diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, sensory challenges directly impact the quality of life [ 14 ], and, therefore, appropriate counseling and early initiation of behavioral interventions can strongly impact patient and family experiences. Finally, many neurodevelopmental disorders have similar or overlapping presentations, and subtle clinical differences, such as sensory features, can be helpful in making a diagnosis or guiding genetic testing [ 3 , 4 , 15 ]. Thus, characterizing the sensory profiles for specific disorders is important for diagnosis and management.…”
Section: Introductionmentioning
confidence: 99%
“…This view was further supported by Cermak and May-Benson (2020) . In addition, Allen and Casey (2017) , Chung (2018) , Delgado-Lobete et al (2020) , and Mikami et al (2021) found relationships between sensory processing difficulties and individuals with DCD, supporting the presence of sensory processing and integration difficulties in individuals with motor coordination challenges. The relationship of motor performance challenges and aspects of QOL was noted as children with DCD were found to have lower HRQOL ( Redondo-Tébar et al, 2021 ) and leisure activity levels ( Raz-Silbiger et al, 2015 ) than their typically developing counterparts.…”
Section: Literature Reviewmentioning
confidence: 64%
“…Participants comprised 68 parents whose children attended the second phase of the Hirosaki Five-Year-Old Developmental Check-up (HFC) Study (See Mikami et al, 2020 [ 19 ] and Saito et al, 2020 [ 20 ] for details) in 2020. The first phase of the annual city-wide developmental screening consisted of a postal questionnaire survey concerning behavioral, emotional, motor, and social development.…”
Section: Methodsmentioning
confidence: 99%